2015
DOI: 10.1021/acsmedchemlett.5b00115
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism/Agonism Modulation to Build Novel Antihypertensives Selectively Triggering I1-Imidazoline Receptor Activation

Abstract: Pharmacological studies have suggested that I 1 -imidazoline receptors are involved in the regulation of cardiovascular function and that selective I 1 -agonists, devoid of the side effects associated with the common hypotensive α 2 -adrenoreceptor agonists, might be considered as a second generation of centrally acting antihypertensives. Therefore, in the present study, inspired by the antihypertensive behavior of our selective I 1 -agonist 4, we designed, prepared, and studied the novel analogues 5−9. A sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…22,23 Our studies also indicated that the introduction of suitable decorations in the ortho position of the phenyl ring conferred to the ligand an interesting profile modulation from antagonism to agonism. Such a modulation was demonstrated both for selective α 2 -AR 24 and I 1 -IBS ligands, 25 suggesting some analogies in the nature of critical binding sites for both systems, as hypothesized by Hieble and Ruffolo. 26 As aforementioned, the simultaneous stimulation of α 2 -ARs and I 1 -IBS might be advantageous for addiction treatment.…”
mentioning
confidence: 56%
“…22,23 Our studies also indicated that the introduction of suitable decorations in the ortho position of the phenyl ring conferred to the ligand an interesting profile modulation from antagonism to agonism. Such a modulation was demonstrated both for selective α 2 -AR 24 and I 1 -IBS ligands, 25 suggesting some analogies in the nature of critical binding sites for both systems, as hypothesized by Hieble and Ruffolo. 26 As aforementioned, the simultaneous stimulation of α 2 -ARs and I 1 -IBS might be advantageous for addiction treatment.…”
mentioning
confidence: 56%
“…In addition, several studies have suggested that I 1 Rs are coupled to G-protein-mediated signal transduction pathways, resulting in the activation of phosphatidylcholine-sensitive phospholipase C (Separovic et al 1997), increased phosphorylation of mitogen-activated protein kinases (MAPK1 and MAPK3) (Zhang and Abdel-Rahman 2005), and inhibition of adenylate cyclase (Greney et al 2000). Activation of any of these second messenger mechanisms in RVLM bulbospinal neurons would result in a decrease in systemic blood pressure (for review, see (Del Bello et al 2015)). I 2 Rs appear to be mainly allosteric binding sites on monoamine oxidases and possibly other proteins (Remaury et al 2000), are distributed throughout the brain, have been associated with glial cells as well as neurons (Lione et al 1998), and are thought to be involved primarily in psychiatric disorders, analgesia, opiate withdrawal, and Parkinson's and Alzheimer's diseases (Garcia-Sevilla et al 1990; Parini et al 1996; Eglen et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Some of these compounds showed interesting in vivo pharmacological properties such as antidepressant 4 and antinociceptive 5 activities, enhancement of morphine-induced analgesia, 6 decrease of both acquisition and expression of morphine tolerance and dependence, 7 as well as hyperanxiety-like behavior after alcohol intoxication, 8 hypotensive and bradicardic effects. 9 …”
Section: Introductionmentioning
confidence: 99%